Metastatic cervical carcinoma presenting as psoas abscess and osteoblastic and lytic bony metastases - George, J. (1995)
A 60-year old Chinese lady presented with a left mass and weight loss. Plain films showed a sclerotic. L1 vertebral body osteopenic L2 and L3 vertebral bodies and loss of left psoas outline. However initially unrevealed history of previous carcinoma of the cervix caused confusions as to the aetiology of a sclerotic vertebrl body associated with an left flank collection. Psoas abscess with adjacent bony osteomyelitis was initially suspected. the left flank mass turned out to be an infected necrotic large metastatic lymph node compressing the lower pole of the left kidney. the sclerotic and osteopenic vertebral bodies represented an unusual presentation of bony cervical carcinoma metastases.